A Modified Sliding Mode Fault Tolerant Control for Large‐Scale Civil Infrastructure. (21st December 2015) - Yeganeh Fallah, Arash; Taghikhany, Touraj
Abstract: Adaptable active control strategies besides advance sensors and actuators technologies lead to higher performance of vibrational control in civil infrastructures under severe ground motions. These resilience control systems are robust against model uncertainties as well as being online recoverable from the malfunctioning of sensors and actuators. In this study, resilient control system based on sliding mode (SM) fault detection observer and SM fault tolerant control is improved for actuator fault in large‐scale systems. The SM fault detection observer is modified for eliminating the excessive chattering in estimating states and actuators' fault, and the reconfigurable SM fault tolerant control is improved to minimizing input forces in H ∞ control framework under seismic action. Design of observer and controller is performed using linear matrix inequalities. Numerical simulations on the cable‐stayed bridge benchmark demonstrate the effectiveness of the proposed fault‐tolerant system. Despite the high order of this large‐scale structure, the proposed fault detection and diagnosis method can effectively find the location and size of faults in actuators without performance degradation and computational costs. The fault‐tolerant controller maintains the performance of the structure at an acceptable level in the post‐fault case by redistribution of control signal to actuators.